The Effect of Baby Massage on the Duration of Breastfeeding for Babies Aged 3-6 Months at Posyandu Kenanga 4, Lembah Sari Village, Cikalongkulon District, Cianjur Regency, Indonesia - Sri Klana; Suparmi (Archives of The Medicine and Case Reports, 2023)
Breastfeeding is a physiological process to provide optimal nutrition to babies, baby massage is an effort to increase the duration of breastfeeding. This study aimed to determine the effect of baby massage on the duration of breastfeeding at Posyandu Kenanga 4, Lembah Sari Village, Cikalongkulon District, Cianjur Regency, Indonesia. This research involved two groups of subjects, one treated with baby massage and a control group. The research results of the 15 respondents in the experimental group, the largest were 9 people (60%) aged 21-35 years, and the smallest were 2 people aged more than 35 years (13.3%), the 15 respondents in the control group were mostly 9 people (60%) aged 21 -35 years old, and the smallest who were over 35 years old were 2 people (13.3%). The majority of babies in the experimental group were 5-6 months old, 9 people (60%). 15 respondents from the experimental group, 13 (86.7%) respondents were healthy and 2 respondents (13.3%) were sick, 15 respondents from the experimental group, 14 (93.3%) had good breastfeeding duration and 1 person (6.7%) had poor breastfeeding duration, 15 respondents in the control group, 10 people (66.73%) had good breastfeeding duration and 5 people (33.3%) had poor breastfeeding duration, 15 respondents in the experimental group, 8 people (53.3%) had normal baby feeding time, 5 people (33.3%) had long baby breastfeeding time and 2 people (13.3%) had a short duration of breastfeeding, 15 respondents in the control group 8 people (53.3%) had a short duration of breastfeeding, 5 people (33.3%) had a normal duration of breastfeeding and 2 people (13.3%) had a long period of breastfeeding, on average The duration of breastfeeding in the experimental group was higher, namely 23.33 with a variation of 3.43 compared to the control group, namely an average of 20.66 with a variation of 2.89. The T-test results obtained a value of p = 0.029. There was a significant difference in the average of the experimental group (getting baby massage) and the control group (not getting baby massage treatment) regarding the duration of breastfeeding.